Dietary practices of children and adolescents with Down syndrome. (June 2018) - Magenis, Marina Lummertz; Machado, Alessandra Gonçalves; Bongiolo, Angela Martinha; Silva, Marco Antonio da; Castro, Kamila; Perry, Ingrid Dalira Schweigert
The aim of this study was to assess dietary intake, breastfeeding history, weight at birth and current weight in children and adolescents with Down syndrome (DS). Therefore, a cross-sectional, controlled study with 19 DS participants and 19 controls without DS matched by gender and age was performed. Except for vitamin D, a lower or the same frequency of insufficient intake in other micronutrients was noted in participants compared with controls. The DS group had a reduced exclusive breastfeeding duration and increased carbohydrate and caloric intake. The consumption of micronutrients in both groups reinforced the current trend of excessive sodium consumption and insufficient intake of calcium, some B complex vitamins and water by children and adolescents.